Wilhelm Rotermund (1843-1925) living in two cultures - Silva, Circe Mary Silva da (2016)
Wilhelm Rotermund belonged to a group of foreigner cultural agents whose goal was to introduce in Brazilian textbooks a practical teaching methodology already used in Germany during the nineteenth century. He was also a driver towards education among German descendants, acting both as book and newspaper editor. We identified possible roots for the methodological ideas that underlie his book Rechenfibel: first Book in arithmetic, published in 1879 in the Province of Rio Grande do Sul, Brazil. To accomplish this goal, we examined books by German pedagogues from the eighteenth century, as Goltzsch and Theel, and compared their proposals regarding arithmetic teaching with Rotermund’s. We verified that pedagogical guidance concerning the intuitive method was present in German works that we have analyzed and also in Rotermund’s book.